Multi-omics analysis identifies CCNB1 as a cell cycle factor driving glioblastoma progression and its inhibition by resveratrol - Bohan Liu; Dazhao Peng; Yankun Chen; Qiuling Li; Yuedong Hu; Shiyu Liu; Huimin Hu (PLoS ONE, 2026)
Glioblastoma (GBM) is a fast-growing primary brain tumor with high mortality and recurrence rates. Dysregulation of the cell cycle is a hallmark of GBM, and cyclin B1 (CCNB1) is a key regulator of the cell cycle. However, the role of CCNB1 in GBM remains unclear. In this study, we found that CCNB1 mRNA and protein expression levels were significantly higher in GBM tissues than normal tissues. High CCNB1 mRNA expression was associated with poorer prognosis in GBM patients. Single-cell and spatial transcriptomics data revealed that CCNB1 + cells represent a proliferative subcluster in GBM, annotated as proliferative cells, and characterized by the upregulation of cell cycle-related pathways. CCNB1 inhibition decreased the proliferation of GBM cells and impaired cell cycle progression from S phase to G2/M. Additionally, resveratrol could inhibit the expression of CCNB1 and its interacting gene polo-like kinase 1 (PLK1). Importantly, through in vitro and in vivo experiments, we found that resveratrol suppressed GBM cell growth with low toxicity. CCNB1 silencing combined with resveratrol treatment further inhibited the proliferation of GBM cells. Collectively, these data suggest that CCNB1 is highly expressed in GBM and may promote GBM progression. Inhibition of CCNB1 may represent a potential therapeutic strategy for GBM.